Comparison of the ability of the King's and MiToS staging systems to predict disease progression and survival in amyotrophic lateral sclerosis. Issue 7 (2nd October 2021) - Luna, Jaime; Couratier, Philippe; Lahmadi, Sanae; Lautrette, Géraldine; Fontana, Andrea; Tortelli, Rosanna; Logroscino, Giancarlo; Preux, Pierre-Marie; Copetti, Massimilano; Benoit, Marin
Abstract: Background: Assessing clinical progression in amyotrophic lateral sclerosis (ALS) remains a challenge. We evaluated the validity and predictive capabilities of the King's and Milano-Torino Staging (MiToS) systems in a cohort of patients with ALS to demonstrate their benefit in clinical practice. Methodology: A cohort study was performed by including ALS incident cases in a referral center from 2007 to 2016. The staging systems were determined at time of diagnosis and follow-up. The standardized median times to reach each stage were computed. A multi-state model in the framework of the Cox model evaluated the predictive value of measurements. The survival C-statistic was reported as a measure of prediction ability. Results: Overall, 298 incident cases were included. The King's and MiToS systems described a progressive increase in the risk of dying with each elapsed stage. However, a lower resolution for late disease description for the King's system was observed, and late stages overlapped for the MiToS system. Slight variations in the staging systems appeared to improve performance based on validity and prediction abilities: (i) in the King's ( C -statistic = 0.783), by adding a new stage involving the need for both gastrostomy and NIV: (ii) in the MiToS ( C -statistic = 0.792), by merging stage 3 and stage 4 into a single stage 3. Conclusion: Both King's and MiToS are valid systems but have certain limitations. Variations in the staging systems may provide a more suitable framework for describing progression and survival. Further research is needed to evaluate the variations in the staging systems.